Flexible polypyrrole activated micro-porous paper-based photoanode for photoelectrochemical water splitting. (16th February 2021) - Thakur, Anupma; Kumar, Praveen; Mouli Thalluri, Sitaramanjaneya; Sinha, R.K.; Devi, Pooja
Abstract: We herein demonstrate polypyrrole decorated micro-porous laboratory filter paper (PFP) as photoanode (PA) for efficient and stable water splitting. The straddling band position with water redox and the measured band gap of ~1.98 eV, make these PFP-PAs effective for water splitting reactions. The results manifest excellent photo-anodic PEC activity of these PFP-PAs, yielding a photocurrent density of ~9.5 mA/cm 2 (at 1.23 V vs. RHE) in a three-electrode configuration. The incident photon-to-current efficiency (IPCE) and applied bias photon-to-current efficiency (ABPE) was measured to be 43.19% and ~1%, respectively. Moreover, the robustness of these flexible PFP-PAs was visualized by the provided stability for more than ~160 min in alkaline conditions. The current study provides a proof-of-concept for the realization of a cost-effective, flexible, and efficient paper-based artificial catalyst (like a natural leaf) for solar-driven water splitting. Graphical abstract: Image 1 Highlights: In-situ fabricated polypyrrole based flexible filter paper photo electrode (PFP-PEs). Exhibit a bandgap of ~1.98 eV and reported as PEs for water splitting. Photocurrent density of ~9.5 mA/cm 2 (at 1.23 V vs. RHE) in 3-electrode system. IPCE and ABPE was measured to be 43.19% and ~1%, respectively. PFP-PEs stable for 160 min in alkaline conditions for PEC water splitting.